A walk in the clouds - Kamen, Robert Mark; Miller, Mark, 1925-; Weitzman, Harvey; Netter, Gil; Zucker, David, 1947-; Zucker, Jerry; Reeves, Keanu; Sánchez-Gijón, Aitana; Quinn, Anthony, 1915-2001; Giannini, Giancarlo; Jarre, Maurice; Arau, Alfonso (Twentieth Century Fox Home Entertainment, 2007)
After returning from World War II, a young G.I. finds he has little in common with the wife he left behind. Disillusioned, he heads north to work as a travelling salesman where he meets the daughter of a wealthy vineyard owner. On her way home, she is terrified of what her father will do when he learns she is unmarried and pregnant. The young man gallantly offers to help by posing as her husband for one night, unaware that doing so will change both of their lives forever.